PDCA – How does the Organization Learn? - Gurabi, Attila; Mátrai, Norbert (International Journal of Engineering and Management Sciences, 2016)
An organisation (whether it is in the private or in the public sector)knows where it is headed, it has a vision. To achieve this vision the organisation can have a strategy beforehand or the vision can be the result of a continuously improving strategy.The strategy can be developed according to the earlier routines or in a totally new way. Many times failures help to find a solution better than the chain of successes. The lessons learned should inevitably be part of the following cycles otherwise the same issues rise again and again which finally ends in exasperation and giving up. When we create a learning process it is easier to focus on avoiding the obstacles than motivation. PDCA is a well-known method for it but what prevents us from applying it the proper way? What are the obstacles that prevent the organisation from developing through its learning processes?